Communicating about clinical trials to culturally and linguistically diverse (CALD) communities: Presenter(s): Robyn Woodward-Kron, University of Melbourne, Australia. (April 2023) - Hajek, John; Story, David
Abstract : Aim/objective: The benefits of clinical trials should be available to all of society. To facilitate this, trial participants need to be representative of society. A body of research has identified significant language and cultural barriers to trial participation for culturally and linguistically diverse communities such as the ethical-legal requirements of recruitment and consent processes. This presentation reports on a program of research and development using digital communication platforms to enhance communication about clinical trial participation. Methods: Three interrelated studies in Melbourne, Australia, informed the design and development of a proof of concept bi-lingual digital platform for informed consent, and in-language web-based informational videos about clinical trials. Interviews with older Italians about their experiences and knowledge of clinical trials informed the development of the prototype, which was evaluated with older Italians in community settings and English speaking patients in an inner city hospital. In the third study, scripts in-language for an informational video were piloted with community members and clinician researchers. Findings: The findings from the interview studies showed that as well as language and cultural barriers, the older Italian participants had little understanding about the purpose of clinical trials. The bi-lingual Italian-English prototype was well received by community members as well as researchers and human research ethics committee (HREC) members. These Findings: informed the development of a short, captioned informational video, Clinical Trials and You, available in English, Vietnamese, Italian, Chinese, and Greek. Discussion: Clinical Trials and You has been endorsed by the HREC of a large Victorian health service, allowing the videos to be uploaded to clinical trial webpages for potential participants to access. Current research involves working with infectious disease clinician researchers to adapt the Clinical Trials and You methodology to participation and consent information for a large multi-centre platform trial.